Correlation Between Media Social Use Intensity with Anxiety on University Students: Pro and Contra - Nugraheni, Teresia Putri Widia; Rana, Aulia; Prameswari, Luh Inten; Magung, Agustina Marielsa; Susanto, Wenly (Journal of Language and Health, 2024)
Social media has become part of people's lives, especially in adolescents and young adults. The increasing use of social media is followed by adaptation problems to serious psychological problems, one of which is anxiety disorders. This disorder can be caused by ongoing social interaction problems so that adolescents experience failure to establish strong relationships with others. However, the exact role of social media use in the occurrence of anxiety is uncertain. This study aims to establish the relationship between social media use and anxiety, and provide recommendations for the use of social media to improve anxiety symptoms. This literature review involves various articles from systematic searches on four search engines. Inclusion criteria include observational or experimental research designs, full-text access, and Indonesian or English in the last 10 years. Meanwhile, exclusion criteria include conference abstracts, literature reviews, opinions, experimental protocols, case reports, and case series and literature more than 10 years. The process of anxiety is an interaction between stressors and biological factors. However, there has been no research that definitively states the role of social media in the brain mechanisms that occur in people with anxiety disorders. Existing studies show negative and positive impacts of social media on anxiety. Based on the research that has been reviewed, researchers recommend limited use of social media and focusing on active interactions, such as effective communication exercises, seeking help, or focusing on positive content. The reviewed studies have not been able to determine the causal relationship between social media use and anxiety. Therefore, further research can use strategies in the form of cohort or experimental study designs, as well as increasing the number and heterogeneity of respondents to strengthen the research. Not only that, further research can be conducted to examine the positive impact of social media and mediating factors between social media use and anxiety, such as personality and childhood.